TREND ANALYSIS OF PRECIPITATION ON CENTRAL CEBU, PHILIPPINES APPLYING MANN-KENNDAL TEST AND SEN'S SLOPE ESTIMATES - Mondejar, Jeremy P. (Journal of Agriculture and Technology Management, 2018)
Please see PDF file.